Constitutional reforms in Uzbekistan during the years of independence - Alikhanov, Mukhammadjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article covers the history of the adoption of the Constitution of the Independent Republic of Uzbekistan, the changes and amendments made to it during the years of independence, and the processes of adoption of the new version of the constitution in 2023 using various articles, works and sources.